The Efficacy of Satureja khuzistanica Essential Oil Treatment in Reducing Escherichia coli O157:H7 Load on Alfalfa Seeds Prior to Sprouting. Issue 2 (6th March 2013) - Taban, Azin; Rahimi, Mohammad Javad; Saharkhiz, Mohammad Jamal; Hadian, Javad; Zomorodian, Kamiar
Abstract Along with the popularity of raw sprouts in the food baskets, the outbreaks associated with the consumption of the contaminated sprouts increased. In the present study, the antibacterial effect of the essential oil of Satureja khuzistanica in reducing the Escherichia coli O157:H7 population on alfalfa seeds prior to sprouting was evaluated. The essential oil (EO) was analyzed by gas chromatography/mass spectrometry. Alfalfa seeds were inoculated with E. coli O157:H7. The inoculated seeds were then treated with different concentrations of the essential oil of S. khuzistanica. The surviving populations of E. coli O157:H7 were enumerated by direct plating of the seeds on tryptic soy agar. The oil was rich in carvacrol. Direct surface‐plating on selective media showed the treatment resulted in a significant (P ≤ 0.05) reduction of E. coli O157:H7 population in a dose‐dependent manner. Increasing the washing time revealed a significant effect on reduction of E. coli O157:H7 population. The considerable antibacterial activity of the oil might be due to the high concentration of carvacrol. As the S. khuzistanica EO did not adversely affect alfalfa seed germination and had a strong antibacterial activity, the oil might be used as a natural antimicrobial product to overcome bacterial contamination of sprouts without compromising the viability. Practical Application During the past decades, existing of chemical antibacterial has become increasingly unpopular in food industries. Consumers presume that these chemicals are threats to human health, because of their carcinogenicity, allergenicity, toxicity and environmental contaminations. For these reasons, nowadays, using of organic products is becoming more popular. Moreover, many foodborne pathogens are genetically adapted to synthetic antimicrobial compounds, thereby reducing the efficacy of such preventatives. It has been known that EOs have antimicrobial activities, rendering these natural products as good alternatives to synthetic bactericides. S. khuzistanica, with high concentration of carvacrol which is classified as GRAS (generally regarded as safe), could be one of these potential alternatives. This antimicrobial property favors its application in food industries as a reasonably safe agent. The confirmed antibacterial activities of S. khuzistanica, recommends its possible application in the field of food preservation for prolonging the shelf life of sprouts during postharvest and marketing processes.